The efficacy of Botulinum Toxin A for limb spasticity on improving activity restriction and quality of life: A systematic review and meta-analysis using the GRADE approach - Baker, J.; Pereira, Gavin (2016)
Objectives: A systematic review and meta analysis using the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach. The aim was to evaluate the efficacy of Botulinum Toxin type A for limb spasticity on improving activity restriction and quality of life outcomes. Data sources: Pubmed, Cinahl, Amed, Embase and Cochrane databases. English Language. Search to January 2015. Review methods: All randomized, placebo controlled trials on adults with active function or quality of life measures for the arm and leg relating to spasticity of any origin and treated with a single dose of Botulinum Toxin A. Evidence quality was assessed by GRADE. Results: Twenty-five studies were reviewed. Meta analysis was carried out on six upper limb and six lower limb studies. Evidence quality for the upper limb was low/very low. A significant result for Botulinum Toxin A was found at four to twelve weeks for the upper limb for active function (SMD 0.32 CI 0.01, 0.62, P=0.04) These effects were maintained for up to six months for Active Research Arm Test (ARAT) only (MD 1.87 CI 0.53, 3.21, P=0.006). Evidence quality was very low for the lower limb. No significant effect was found. Meta analysis was not possible for quality of life measures. Conclusion: Botulinum Toxin A may improve active outcomes in the upper limb but further evidence is needed. No conclusion can be drawn about the effect on active outcomes for the lower limb or for quality of life measures in either limb.